2020
DOI: 10.1051/meca/2020017
|View full text |Cite
|
Sign up to set email alerts
|

A multiobjective optimization of journal bearing with double parabolic profiles and groove textures under steady operating conditions

Abstract: The double parabolic profiles can help journal bearing to reduce bushing edge wear, but it also reduces load carrying capacity and increases friction loss. To overcome these drawbacks, in this study, a multiobjective optimization of journal bearing with double parabolic profiles and groove textures is researched under steady operating conditions using Taguchi and grey relational analysis methods. Firstly, a lubrication model with journal misalignment, elastic deformation, asperity contact, thermal effect is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Kango et al [16] found that microgrooved journal bearing can reduce the friction coefficient and average temperature better than spherical textured journal bearing, and the performance gain is more obvious at lower eccentricity ratio. Researchers [17][18][19] used a multiobjective optimization method to optimize the texture parameters of the microgrooved journal bearing to obtain greater load-carrying capacity and smaller friction coefficient. Lately, Filgueira Filho et al [20] experimentally analyzed the performances of textured journal bearings with chevron, saw tooth, oblong dimple, and aligned dimple and found that the chevron textured journal bearing exhibited smaller eccentricity under reasonable texture geometrical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Kango et al [16] found that microgrooved journal bearing can reduce the friction coefficient and average temperature better than spherical textured journal bearing, and the performance gain is more obvious at lower eccentricity ratio. Researchers [17][18][19] used a multiobjective optimization method to optimize the texture parameters of the microgrooved journal bearing to obtain greater load-carrying capacity and smaller friction coefficient. Lately, Filgueira Filho et al [20] experimentally analyzed the performances of textured journal bearings with chevron, saw tooth, oblong dimple, and aligned dimple and found that the chevron textured journal bearing exhibited smaller eccentricity under reasonable texture geometrical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have investigated the performance of dynamic journal bearings under the effect of microtexture. For example, Chongpei, Ning and Wanyou et al [15,16] proposed a new type of double parabolic profiles with groove textures and theoretically investigated the bushing deformation and lubricating oil temperature variation using a suitable model, and the results showed that the appropriate texture position and geometry could improve the load carrying capacity of dynamic journal bearings and reduce the wear of bushing edge. Guo and Yanfeng et al [17] studied the modeling of coupled microtexture journal-thrust bearings lubricated with water and found that not only the coupled hydrodynamic effect could improve the lubrication performance of the bearings, but also there existed an optimal bottom shape of the microgroove that could improve the lubrication performance of the bearings, in addition to an optimal value of the microgroove depth produced maximum load carrying capacity and minimum friction coefficient of the bearings.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Harvey et al (2018) used the interior-point algorithm to numerically optimise the depth, circumferential and radial extent of bearing surface texture. Liu et al (2020) studied the optimal combination of the number, depth and diameter of double parabolic texture based on the Taguchi and grey correlation analysis method. Zhang et al (2017) optimised the contour of surface micro-dimples based on the average Reynolds equation and genetic algorithm.…”
Section: Introductionmentioning
confidence: 99%